Can Intra-articular Injection of Glucocorticoids Be an Alternative Intervention to Achieve Remission in Patients With Rheumatoid Arthritis Exhibiting Low Disease Activity? A Single-Center Longitudinal Study. Issue 2 (4th March 2022) - Kishimoto, Yuji; Kato, Yoshihiro; Uemura, Manami; Kuranobu, Koji
Abstract : Background/Objective: This study aimed at investigating whether a single intra-articular (IA) injection of triamcinolone acetonide (TA) could facilitate to achieve clinical remission in patients with rheumatoid arthritis (RA) exhibiting low disease activity (LDA). Methods: This longitudinal study included 22 patients with RA exhibiting LDA involving wrist arthritis at our institution between April 2016 and March 2019. A single IA injection of 20 mg TA was administered into the symptomatic wrist joint. Efficacy was assessed by the primary end point of proportion of patients reaching clinical remission. Secondary end points included Clinical Disease Activity Index (CDAI), Simplified Disease Activity Index (SDAI), Health Assessment Questionnaire Disability Index, adverse events, and ultrasonographic assessment of the injected wrist joints. Results: Remission rates were 40% and 50% at weeks 4 and 12, respectively, and were maintained at approximately 50% until week 24. The secondary outcomes of CDAI, SDAI, and Health Assessment Questionnaire Disability Index were improved significantly at week 4, and the improvements in CDAI and SDAI continued up to week 24. Ultrasonography showed that synovial hypertrophy, power Doppler signals, and the combined score were significantly reduced at weeks 4, 12, and 24 compared with the baseline. No patient developed severe, irreversible adverse events. Conclusions: Approximately half of the patients with RA exhibiting LDA who received a single IA injection of TA into the wrist joints achieved clinical remission without serious adverse events in the midterm period, suggesting that IA injection of TA might be considered as an alternative intervention to achieve remission in patients with RA exhibiting LDA.